Employment relationships as the centrepiece of a new labour policy paradigm - Graham S. Lowe (HR Resources Database, 2002)
This paper examines changes in employment relationships in Canada during the late 20th century. Despite well documented transformations in labour market structures and work contexts, we are only now grasping the significance of these trends for the relationships between workers and employers. Considerable debate revolves around the extent and nature of new employment relationships. Still, it is clear that fewer workers fit the historical benchmark of the post-WWII 'standard employment model'. Consequently, the labour and employment policy framework fashioned during the post-war decades no longer meets the needs of an increasingly differentiated workforce. Furthermore, the current policy emphasis on learning and skills for innovation and productivity requires a fuller understanding of how trust, communication and other elements of employment relationships mediate human capital development. The ideal focus for the next generation of labour policy must be the workplace, which is where relationships among coworkers and between workers and management can either hinder or enable the achievement of major social and economic goals.